2015
DOI: 10.1002/lary.25411
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal outcomes in obstructive sleep apnea syndrome

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
2
21
1
Order By: Relevance
“…Although the differences did not reach the chosen level of significance it indicates a clear association between nasal complaints and severity of disease. This verifies the results in the study by Kuan et al where sinonasal complaints evaluated by the SNOT-22 score seemed to be correlated to OSA severity [1]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the differences did not reach the chosen level of significance it indicates a clear association between nasal complaints and severity of disease. This verifies the results in the study by Kuan et al where sinonasal complaints evaluated by the SNOT-22 score seemed to be correlated to OSA severity [1]. …”
Section: Discussionsupporting
confidence: 91%
“…Sinonasal complaints are associated with obstructive sleep apnea (OSA) [1], and the relief of sinonasal obstruction has been shown to reduce subjective complaints of daytime sleepiness [2]. Excessive daytime sleepiness is one of the main symptoms in obstructive sleep apnea syndrome and a major concern due to the strong association with a reduction in motor skills such as handling vehicles and machines [3].…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive obstructive episodes cause ischemia‐reperfusion injury to the airway, all the while OSA patients have increased systemic inflammatory mediators predisposing the soft tissues to free‐radical development . These same theories have been proposed recently for two small cohort samples finding higher levels of sinonasal complaints in OSA patients, though no study has definitively linked OSA and higher rates of sinusitis. It is worth mentioning that a separate study of our cohort found no difference in sinusitis QOL scores (by Sino‐Nasal Outcome Test) between OSA and non‐OSA patients.…”
Section: Discussionmentioning
confidence: 88%
“…4 The SNOT-22 questionnaire interrogates patients on rhinologic, nonrhinologic-otolaryngic, psychological, and sleep functions. 4,5 We used these 4 "subdomains" for our analyses, following the individual item categorization described by Hopkins et al 4 and Kuan et al 6 : rhinologic (need to blow nose, sneezing, runny nose, nasal obstruction, loss of smell/taste, postnasal drip, thick nasal discharge), nonrhinologic-otolaryngic (cough, ear fullness, dizziness, ear pain, facial pain/pressure), sleep function (difficulty falling asleep, waking up at night, lack of good night's sleep, waking up feeling tired), and psychological (fatigue, reduced productivity, reduced concentration, frustration/restlessness/irritability, sadness, embarrassment). The magnitude of CRS burden on sinus CT scan was calculated using the Lund-Mackay staging system; total scores range from zero (no disease) to a maximum of 24 points.…”
Section: Methodsmentioning
confidence: 99%
“…We used these 4 “subdomains” for our analyses, following the individual item categorization described by Hopkins et al . and Kuan et al …”
Section: Methodsmentioning
confidence: 99%